PENGGUNAAN MICROSOFT EXCEL DALAM ANALISIS DATA EKSPERIMEN PADA PEMBELAJARAN FISIKA - Yosaphat Sumardi (Jurnal Cakrawala Pendidikan, 2002)
Microsoft Excel is one of the application programs calledspreadsheets, which enable users to supply data and instructionsin the form of commands and formulas to make the desired computationsA spreadsheet is nbt a computer langage used to writea program, it is an application program with which a user canorganize procedures for making calculations in a tabular formMicrosoft Excel is a powerhl program that can be used toanalyze data of an experiment in physics This applicationprogram is quite easy lu use and it is supported by adequate internalutilities for making calculations and graphs.Many kinds of data from experiments in physics can be analyzedwith the help of the application program Microsoft Excel.Various calculations can be done rapidly and easily by putting touse the internal hnctions in this application program An analysisfitting a curve to batches of experimental data can also bedone by using the graph utility